Autoimmune correlation of rheumatoid arthritis and periodontitis - Lalitha Tanjore Arunachalam (Wolters Kluwer Medknow Publications, 2014)
Rheumatoid arthritis and periodontitis, both, chronic inflammatory diseases share certain common diagnostic, pathological, immunogenetic and therapeutic features. A recently discovered enzymatic mimicry between human and bacterial species is novel and it opens up a new terrain for therapeutic blockade in the management of rheumatoid arthritis.